O controlo de gestão na hotelaria portuguesa - Nunes, Catarina Rosa (2010)
Submitted by Bruno Marçal (bruno.marcal@iscte.pt) on 2010-08-24T11:46:20Z No. of bitstreams: 1 Dissertação Catarina Nunes.pdf: 540309 bytes, checksum: 37249794b8b6bb984e1949e435535649 (MD5)